SEVERAL ISSUES OF TEACHING GYMNASTICS IN MIDDLE SCHOOLS (American Journal of Technology and Applied Sciences, 2024)
What should be paid attention to in the more effective organization of gymnastics classes in general secondary schools of our republic, what methods should be used when conducting classes, and medical groups in physical education? The state of students' sports preparation and stages.